“A Din and a Dirdy, a Garray and a Hirdy Girdy”: the specifics of the composition of pars prima of the Scottish mock epic "Colkelbie Sow" - Vadim Semyonov (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The article deals with «Colkelbie Sow», the epic poem of the 15th century, created by an anonymous author in Middle Scots. The Anglo-Scottish publishers of this mock-epic perceived the poem as strange, incomprehensible, with a bizarre composition. Therefore, its plot and narrative structure became the subject of our study. The research methods are historical poetics, versification and linguopoetics. The main attention was focused on the vaguest part of the poem - Pars Prima. The study revealed significant differences between this part and the Proemium and the following parts. The differences are manifested in its plot inconsistency with the rest of the parts, in its special verse forms, the special tone of the narration and the position of the narrator regarding the subject of the narration, as well as in the frame text. Their discovery made it possible to assume the early existence of Pars Prima as a separate and complete work in relation to the full multi-part text of the poem that is known today. The secondary subjects of the research were the compositional device of the enumeration, which outgrew the functions of form and turned into the core and purpose of the plot, and the euphony of nominations, achieved by combining them into pairs of words with a common initial. This poem is underestimated and therefore little studied even by English philologists, and in Russian literary criticism this article is its pilot study.